2017
DOI: 10.1111/pce.13068
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how viruses enhance plants' resilience to drought and the limits to this form of viral payback

Abstract: This article comments on: Virulence determines beneficial trade-offs in the response of virus-infected plants to drought via induction of salicylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Several studies have reported increased plant tolerance to abiotic stresses, including water deficit, upon infection by viruses [4,30,32]. Across the quite large number of plant accessions assayed here (n = 44), we did not find any significant positive effect of CaMV infection on plant tolerance to water deficit in terms of vegetative biomass production (see position of accessions relative to line of equal response on S4B Fig).…”
Section: Survival But Not Reproductive Effort Of Infected Plants Iscontrasting
confidence: 43%
See 2 more Smart Citations
“…Several studies have reported increased plant tolerance to abiotic stresses, including water deficit, upon infection by viruses [4,30,32]. Across the quite large number of plant accessions assayed here (n = 44), we did not find any significant positive effect of CaMV infection on plant tolerance to water deficit in terms of vegetative biomass production (see position of accessions relative to line of equal response on S4B Fig).…”
Section: Survival But Not Reproductive Effort Of Infected Plants Iscontrasting
confidence: 43%
“…In contrast with Grime's expectations, the effects of water deficit on plant development and leaf physiology may reduce virus systemic spread, and therefore decrease virulence [13,28,29]. Virus-induced drought tolerance has been demonstrated in several species infected with different viruses [4,[30][31][32][33]. Recent findings in Arabidopsis thaliana demonstrated that spread of Cauliflower mosaic virus (CaMV; Caulimoviridae, a non-circulative virus transmitted by aphids that infects essentially plants of the family Brassicaceae) infection throughout the host plant was slower under water deficit, though the combined effects of CaMV infection and water deficit remained more detrimental to growth compared with either viral infection or water deficit alone [13].…”
Section: Plos Pathogensmentioning
confidence: 89%
See 1 more Smart Citation
“…Perennials can suffer multi-year fitness impacts of viruses, especially viruses whose prevalence in wild communities is driven by amplification in adjacent annual cropping systems (Alexander et al, 2013; Malmstrom and Alexander, 2016; Malmstrom et al, 2017). Alternatively, known and novel viruses may contribute to the drought and heat tolerance characteristics of their hosts (Xu et al, 2008; Davis et al, 2015; Carr, 2017). Both possibilities remain underexplored for wild plants, but manipulative studies with our candidate hosts and their pathogens are now possible with the resources provided by our case study.…”
Section: Resultsmentioning
confidence: 99%
“…To date, environmental conditions and plant physiological mechanisms that can lead to contrasted relationship with viruses, from mutualism to increased pathogenicity, remain poorly studied ( Roossinck, 2015 ). Few recent investigations combining abiotic and biotic stresses clearly demonstrate that in addition to factors related to the virus and plant genotype the fate of plant–virus interactions also depends on the abiotic environment ( Prasch and Sonnewald, 2013 ; Ramegowda and Senthil-Kumar, 2015 ; Fraile and García-Arenal, 2016 ; Aguilar et al, 2017 ; Carr, 2017 ). A growing body of data is uncovering the intimate entanglement of the plant physiological pathways involved in responses to various abiotic stresses and in defense against pathogens and herbivores ( Bostock, 2005 ; Pandey et al, 2015 ; Nejat et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%